Dialogue, Worldview Inclusivity, and Intra-Religious Diversity: Addressing Diversity through Religious Education in the Finnish Basic Education Curriculum - Ubani, Martin (Religions, 2020)
The purpose of this article is to discuss how religious and non-religious diversity are addressed in the current national core curriculum for religious education (RE) in basic education in Finland. We first discuss the educational developments behind the Finnish curricular reform, and then focus on issues related to RE and RE research in Finland. We then describe the key contextual contributors to the current RE curriculum in basic education before proceeding to examine how diversity is addressed in the curriculum. Based on our examination, we identify four themes in the curriculum: inter-religious diversity, religious and non-religious worldviews, cultural diversity, and dialogue skills. In RE, diversity is largely addressed within a framework of religion and multiculturality. The article ends with a call for renewal of research foci in RE.